Pelaksanaan Tindakan Diversi dalam Penanganan Perkara Anak di Bandar Lampung - Amelia Dini Asri (KEADILAN PROGRESIF, 2017)
Arrest, detention, and conviction of the child should be the last choice of law enforcement related, to avoid criminal child passed to the formal criminal justice system. It requires alternative problem solving children in conflict with the law through diversion efforts. Practical application the juvenile diversion in Polresta Bandar Lampung have not been fully implemented for all children, especially the criminal case after the release of Secret Telegram Kapolda Lampung No: STR / 22 / XI / 2006 / DITRESKRIM which in practice is still encounter various barriers. Based on the results of the background is at issue in this paper is the case how are the children that can be applied to the act of diversion, how the implementation of the procedure in case of diversion measures Reg No: LP/4574/X/2012 in Polresta Bandar Lampung, and why it happened barriers in the implementation of cases of child diversion in Bandar Lampung.Approach the problem in this study using normative approach and empirical juridical approach though library research, with sources from Polresta Bandar Lampung, Balai Pemasyarakatan (BAPAS) Class II Bandar Lampung and LembagaPerlindungan Anak (LPA). The data were analyzed qualitatively.Case Reg No: LP/4575/X/2012 on behalf of the defendant Yono (not his real name) and Melati (not her real name) has applied for diversion settlement through mediation. Together with BAPAS parties, the victim and the perpetrator parents and LSMs, investigators conduct deliberations to determine peace. After the mediation, Melati’s family declare peace with Yono’s family and has made a statement in the form of peace deal between the Melati’s  family with Yono’s family agreement to pay all labor costs Melati. Peace involves Lurah, RT, Babinkamtibmas, and the Lembaga Perlindungan Anak (LPA). Category of offense punishable by one year should be prioritized for implementation of diversion and criminal offenses punishable 1 (one) to 5 (five) years may be considered for diversion application. Barriers to implementation is the lack of capability of knowledge diversion law enforcement authorities, parties of the society can not be consulted and fully devolved matter son to the authorities, the families of the victim and the perpetrator's family for the difficult compromise, and the lack of full government’s concern about the existence of the Institute of Social and good coordination with the legal advisor.For law enforcement officers are suggested for the benefit of legal protection for the child, then it should have been an excellent coordination between kemasyarakatan counselors, investigators, prosecutors and judges in accordance with the duties and authority as well as their respective functions under the law. Government in handling cases children are many things that must be considered especially things concerning the future of the children themselves so that what is stated in the Indonesia Law of Child Protection and the Indonesia Law Juvenile Criminal Justice System should be actually implemented that can foster children in trouble with the law in accordance with the provisions of the Indonesia Law of Child Protection, so that the imposition of unnecessary imprisonment.